ASPIRASI RAKYAT DAN REFORMASI PARLEMEN - Yusuf, Al Muzzammil (Pusat Penelitian Politik, 2011)
Survey shows that Indonesian citizens are not satisfied with the performance of their Parliament becausethe Members ofParliament do not do their function optimally in legislating controlling and budgeting It createsa democratic deficit Therefore a parliamentary reformation based on aspiration and participation of Indonesian citizens is very much needed The Reformation will be done through Policy Products Some ofthosepolicyproducts are including issuing Law that pro citizen strengthening public participation in controlling process ofthe Executive Board and using Media optimally as tools for political socialization and communication towardsIndonesian citizens